The switching of strong spin wave beams in patterned garnet films - R. Gieniusz (Nature Portfolio, 2017)
Abstract The application of spin waves in communication with information encoded in amplitude and phase could replace or enhance existing microelectronic and microwave devices with significantly decreased energy consumption. Spin waves (SW) are usually transported in a magnetic material shaped to act as a waveguide. However, the implementation of SW transport and switching in plane homogeneous magnetic films and running as a narrow beam with a small divergence angle still present a challenge. We propose a realization of a strong SW switchers based on a patterned yttrium iron garnet (YIG) film that could serve as a magnonic fundamental building block. Our concept relies on the creation of a narrow beam of relatively short-wavelength SW by effect of a total non-reflection, found to be tied to refraction on the decreasing internal magnetic field, near a line of antidots at YIG. Nonreciprocal SW excitation by a microstrip antenna is used for controlling the direction of the signal flow. We demonstrate unique features of the propagation of microwave-excited SW beams, provide insight into their physics and discuss their potential applications in high-frequency devices.